A lateral remelting phenomenon of the primary phase below the temperature of peritectic reaction in directionally solidified Cu–Ge alloys. Issue 23 (20th November 2013) - Wang, Shujie; Luo, Liangshun; Su, Yanqing; Guo, Jingjie; Fu, Hengzhi
Abstract: Abstract : During peritectic solidification, besides the longitudinal remelting of the primary phase at the temperature of peritectic reaction $\left( {T_{\rm{p}}^K} \right)$, a lateral remelting phenomenon of the primary phase below $T_{\rm{p}}^K$ is observed under high velocity in directionally solidified Cu–Ge alloys. The lateral remelting occurs continuously along a liquid channel as temperature decreases, and the lateral remelting velocity is larger than that of peritectic transformation. The lateral remelting leads to the morphological change of the primary dendrites, even the fragmentation of dendrite arms. The phenomenon also means that the classical theory calculating the volume fraction of the primary phase during peritectic transformation can need to be modified under some conditions. However, under low velocity, the phenomenon is not so significant. The phenomenon is explained by means of solidification and remelting theory.